Cover Image: Volume 34 Issue 7. Issue 7 (18th July 2019) - Chemtob, Raphaelle A.; Mick, Stephanie; Gillinov, Marc; Hodges, Kevin; Wierup, Per
Abstract : Cover Caption : The cover image is based on the Surgical Technique Repair of bileaflet prolapse in Barlow syndrome: The 4‐chord technique by Per Wierup et al., https://doi.org/10.1111/jocs.14078